Partial sequencing of the VP2 capsid gene for direct enterovirus genotyping in clinical specimens. (8th February 2014) - Ibrahim, W.; Boukhadra, N.; Nasri‐Zoghlami, D.; Berthelot, P.; Omar, S.; Bourlet, T.; Pozzetto, B.; Pillet, S.; Zupanc, T. A.
Abstract Typing of human enterovirus (EV) remains a major goal for diagnostic and epidemiological purposes. Whereas sequencing of the VP1 coding region is the reference standard for EV typing, a method relying on sequencing of the VP2 coding region has been proposed as an alternative; however, this has been validated only on cell culture supernatants. To avoid the selection of cultivable strains and to quicken the identification step, a new semi‐nested PCR method targeting the VP2 region was developed by use of the CODEHOP strategy. After validation of the method on reference and clinical strains, a total of 352 clinical specimens found to be positive for EV RNA (138 with the GeneXpert EV kit and 214 with the Enterovirus R‐gene kit) during a 3‐year period (2010–2012) were analysed prospectively for VP2 genotyping. Overall, 204 (58%) specimens were typeable. A higher proportion of throat swab/stool specimens than of cerebrospinal fluid (CSF) specimens was found to be typeable (94 of 142 (66.2%) vs. 83 of 169 (49.1%), respectively, p <0.01 by the chi‐square test). Moreover, the median Ct value obtained was lower for typeable specimens than for untypeable specimens (32.20 vs. 33.01, p <0.05, and 25.96 vs. 31.74, p <0.001, for the GeneXpert and R‐gene tests, respectively, by the Mann–Whitney–Wilcoxon test). These results suggest that, in cases of EV meningitis, a peripheral specimen (i.e. throat swab or stool) that is susceptible to exhibiting a higher viral load should be used in preference to CSF for identifying the causative EV genotype by use of the VP2 typing method without cell culture isolation.